PENGARUH DISIPLIN, MOTIVASI DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI KERJA KARYAWAN PADA DEPOT FP LPG PERTAMINA TANDEM - Halomoan Sinaga (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2016)
Depot FP LPG Pertamina Tandem is a company engaged in the field of gas that can notbe separated from issues including declining discipline, lack of motivation and emotionalintelligence that employees have not been implemented effetively so that the employee’sperformance is not optimal effecting employee performance. And the problems of this studyare variable disciplin, motivation and emotional intelligence simyultaneously positive andeffect significantly to job performance of employee on Depot LPG Pertamina Tandem. Thepurpose of this study is to identify the extent of the influence of discipline, motivation andemotional intelligence on job performance of employee Depot FP LPG Pertamina Tandemto compare the theory that the author has been studied in college. This study used a sampleconsist of 65 respondents. At amounted to 0.856 while t t1.984 and significant probability is 0,000, sot0.856 > 0.05, it is concluded Tolak Ho (terima Hi), disciplin effect particially.tis equal 3.039 whilet1.984 and significant probability amounted to 0.000 t> 0.05, it can be concluded tolak Ho (terima Hi). Motivation effect particially. Att= 1.984 and significant probability is amounted to 0.000t=386 > 0.05, it can be concluded tolak Ho (terima Hi). Emotional intelligence effect particially.